2009
DOI: 10.1007/s10856-009-3956-1
|View full text |Cite
|
Sign up to set email alerts
|

Bio-corrosion characterization of Mg–Zn–X (X = Ca, Mn, Si) alloys for biomedical applications

Abstract: The successful applications of magnesium-based alloys as biodegradable orthopedic implants are mainly inhibited due to their high degradation rates in physiological environment. This study examines the bio-corrosion behaviour of Mg-2Zn-0.2X (X = Ca, Mn, Si) alloys in Ringer's physiological solution that simulates bodily fluids, and compares it with that of AZ91 magnesium alloy. Potentiodynamic polarization and electrochemical impedance spectroscopy results showed a better corrosion behaviour of AZ91 alloy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(62 citation statements)
references
References 32 publications
2
57
0
3
Order By: Relevance
“…A number of materials have been studied in the design of surgical clips in other areas. Stainless steel clips and materials such as titanium and tantalum have been used for example to ligate the cystic duct and artery in laparoscopic cholecystectomy (Charara, Dion et al 1994) However, some limitations of these materials include significant foreign body reaction, poor holding power and significant interference with roentgenologic studies like computerized tomography (CT) and magnetic resonance imaging (Klein, Jessup et al 1994;Min Tan and Okada 1999;Pietak, Staiger et al 2006;Rosalbino, De Negri et al 2010). The introduction of ligating clips manufactured from novel polymers such as polydioxanone in laparoscopic cholecystectomy helped to address these limitations.…”
Section: New Vocal Fold Wound Closure Device -Bioabsorbable Microclipsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of materials have been studied in the design of surgical clips in other areas. Stainless steel clips and materials such as titanium and tantalum have been used for example to ligate the cystic duct and artery in laparoscopic cholecystectomy (Charara, Dion et al 1994) However, some limitations of these materials include significant foreign body reaction, poor holding power and significant interference with roentgenologic studies like computerized tomography (CT) and magnetic resonance imaging (Klein, Jessup et al 1994;Min Tan and Okada 1999;Pietak, Staiger et al 2006;Rosalbino, De Negri et al 2010). The introduction of ligating clips manufactured from novel polymers such as polydioxanone in laparoscopic cholecystectomy helped to address these limitations.…”
Section: New Vocal Fold Wound Closure Device -Bioabsorbable Microclipsmentioning
confidence: 99%
“…However, as pure magnesium has been found to corrode too quickly in the low pH environment of physiological systems, much effort has also been placed into developing alloys or coatings to limit its degradation behaviour (Zeng, Dietzel et al 2008). Rosalbino et al (Rosalbino, De Negri et al 2010) reported improved corrosion behaviour of Mg-ZnMn alloys for orthopaedic implants. Kannan et al (Kannan and Raman 2008) studied the corrosion of AZ series (Al and Zn) magnesium alloys with the further addition of Ca, reporting significantly improved corrosion resistance with a reduction in mechanical properties (15% ultimate tensile strength and 20% elongation before fracture).…”
Section: New Vocal Fold Wound Closure Device -Bioabsorbable Microclipsmentioning
confidence: 99%
“…Zinc is -next to aluminium -one of the most used alloying elements with the advantages, such as increase of the strength of Mg alloys, improvement of the castability [8,[13][14][15]. Besides, the addition of zinc leads to enhancement of corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [16][17][18][19] showed that optimum amount of zinc with appropriate mechanical and corrosion properties is about 4 wt.%. In addition, zinc and calcium can be well metabolized by human body [14], which makes them more attractive for their using as effective alloying element of magnesium. From the wide spectrum of possible thermo-mechanical processes, the extrusion was selected as one of the most used large-scale manufacturing methods, which enables to convert a cast billet to a finished wrought product [7].…”
Section: Introductionmentioning
confidence: 99%
“…In order to adjust the corrosion rate of magnesium, modifications such as metal working, alloying, and coating are commonly performed to improve magnesium's corrosion resistance [14][15][16]. It is known that the addition of zinc (Zn) and manganese (Mn) can increase the mechanical strength and corrosion resistance for the conventional metal alloys.…”
Section: Introductionmentioning
confidence: 99%